Charakter społeczno-gospodarczy miast powiatu łódzkiego i łęczyckiego 1807–1869 - Kula, Witold (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2019)
In the years 2020–2021, Łódź and other surrounding cities will celebrate the 200th anniversary of the decisions made by the authorities of the Kingdom of Poland, aimed at the industrialization of this part of Polish territory. Some of these urban centers, such as Lodz, have been successful, while most of them have not been able to develop industrially. Witold Kula, an excellent researcher of socio-economic history, wrote about these issues. So far this work has not been published and thanks to the help of prof. Marcin Kula, the author’s son, was published in a journal. W. Kula decided to analyze the economic and social condition of the cities located within the Łódźand Łęczyca poviats (according to the administrative status of 1921). Therefore, he was interested in the area subjected to industrialization and protection policy by the authorities of the Kingdom of Poland under the Act of Governor Józef Zajączek of 1820. The author was looking for an answer to the fundamental question which of the cities located in this area were also in the legal sense and in economic terms, and which and from an economic point of view, they did not differ from the status of a village? The conclusions and reflections contained in the work cover a long chronological period, starting from 1807 and ending with 1869, i.e. from the moment of placing Polish cities under the administration of a modern bureaucratic national magistracy, to the year in which the tsarist decree was issued to rename some settlements. cities in the governorates of the Kingdom of Poland. The subject of this work were 13 cities, namely: Grabów, Kazimierz (Łęczycki), Łęczyca, Łódź, Parzęczew, Piątek, Rzgów, Tuszyn and Zgierz, and the cities elevated to the rank of cities during the Congress Kingdom: Ozorków (1816), Aleksandrów and Poddębice (1822), Konstantynów (1830). After the reform of 1869–1870, only four of them remained towns: Łęczyca, Łódź, Ozorków and Zgierz. In implementing the theme, W. Kula assumed the following stages: “1. Overview of the basic and existing definitions of the term «city»; 2. on this basis, determining the basic economic and demographic characteristics of the city, and thus the qualification criteria of the city; 3. establishing the facts corresponding to the successful qualification criteria in individual cities in a particular period of time”. The author did not intend to issue “a firm sentence on each of the examined cities, granting or denying it the right to the” title “of the city in the economic sense. More important for him was to “establish the actual state of affairs corresponding to individual criteria, the state which, using these criteria, will sometimes lead us to various conclusions”. The work of W. Kula was based on a variety of source material, primarily the resources of the then pre-war archives, which were partially lost as a result of the tragic consequences of the Second World War. Hence, this monograph is also extremely important because it provides contemporary researchers with invaluable source material for further analyzes of the history of the cities of the Łódź region. More than a hundred tables included in the work by W. Kula with various and valuable statistical data will help in this. The monograph published in print consists of an extensive part called Introduction, divided into two chapters, the first of which is entitled Issue, and the second - Sources and studies, and two parts. The first part is entitled The economic content of the term “city” and is also divided into the following two chapters: Existing definitions of the term “city” and Eligibility criteria for urban settlements. On the other hand, the second, entitled Socio-economic character of cities in the Łęczyca and Łódź poviats, is the main part of the monograph with a source analysis of 13 cities and towns under consideration. It opens with Introductory remarks, followed by an alphabetical list of the aforementioned urban centers in terms of economic and social aspects in the following 13 sections. The work is supplemented by a bibliographic list and a list of abbreviations. The editors of the journal made only minor interference in the work by correcting typos and the so-called Czech errors, as well as by modernizing the spelling and the scientific apparatus of the monograph (in the notation of footnotes and bibliographic items), e.g. by supplementing some items, introducing currently used abbreviations, etc. Moreover, the bibliographic list that opened the work in the manuscript was moved to its end. However, no linguistic and stylistic corrections were made to reflect the character of the writing style and the way of expressing thoughts as accurately as possible by W. Kula, then a young adept of the historical guild.